HPLC-PDA-MS/MS profiling of secondary metabolites from Opuntia ficus-indica cladode, peel and fruit pulp extracts and their antioxidant, neuroprotective effect in rats with aluminum chloride induced neurotoxicity - El-Hawary, Seham; Sobeh, Mansour; Badr, Wafaa K.; Abdel-Fattah, Mohamed; Ali, Zeinab Y.; El-Tantawy, Mona E.; Rabeh, Mohamed A.; Wink, Michael (Saudi journal of biological sciences, 2020)
Opuntia ficus-indica (L.) Mill. (OFI), also known as Indian fig Opuntia or prickly pear, is a member of the family Cactaceae that produces edible, nutritionally rich sweet fruits. It has been traditionally used to treat several health disorders and is considered to possess various therapeutic properties. In this work, we have characterized 37 secondary metabolites using HPLC-MS/MS, identified the polysaccharide from the fruits and cladodes pulp, and estimated the neuroprotective activity. All tested extracts exhibited substantial antioxidant activities in-vitro and neuroprotective potential in AlCl3 induced Alzheimer’s condition. Administration of OFI extracts attenuated AlCl3 induced learning and memory impairment as confirmed from passive avoidance test and counteracted the oxidative stress as manifested from decreasein the elevated MDA level, increased TAC, GSH, SOD and CAT levels. OFI extracts significantly decreased the elevated brain levels of proinflammatory cytokines (NF-κβ and TNF-α), increased anti-inflammatory cytokine (IL-10), and monoamine neurotransmitters (NE, DA, 5-HT) as compared to positive control group. The extracts showed a significant decrease in acetylcholinesterase level (AChE) as compared with AlCl3. Furthermore, molecular docking was performed to investigate the ability of the major constituents of OFI extracts to interact with acetylcholinesterase (AChE) and serotonin transporter (SERT). Among the tested extracts, cladodes contain highest phenolic content and exhibited the highest antioxidant, anti-inflammatory and neuroprotective activities, which could be attributed to presence of several polyphenols, which could function as AChE and SERT inhibitors. Opuntia ficus-indica might be promising candidate for treating Alzheimer disease, which makes it a subject for more detailed studies.
Gesehen am 15.10.2020